Experiences with rehabilitation and impact on community participation among adults with physical disability in Colombia: perspectives from stakeholders using a community based research approach - María Luisa Toro-Hernández; Alejandra Mondragón-Barrera; Sara Múnera-Orozco; Laura Villa-Torres; Wendy Camelo-Castillo (BMC, 2019)
Abstract Background Despite representing 70 million people in Latin America, access to comprehensive rehabilitation and participation in the community remains a challenge for persons with disability (PWDs) in the region. Through enactment of the Disability Law, Colombia has made improvements to recognize and address some of the barriers for PWDs, including access to comprehensive rehabilitation. However access remains limited with significant disconnect between perspectives of various stakeholders and the needs of the population. We examined the unique perceptions on access to comprehensive rehabilitation services and participation of PWDs. We also explored the perspective of caregivers of PWDs, rehabilitation professionals, and other stakeholders on the experiences of PWDs. Our goal was to identify gaps in the implementation of comprehensive rehabilitation programs, and barriers to access resources for comprehensive rehabilitation or services that would impact participation of PWDs. Methods Qualitative study conducted in 2017. Data was collected from a purposive sample of adults with physical disability, aged 18-44 years, who had received rehabilitation services at a local partner organization and with different backgrounds and experiences with disability. Purposive sampling was also conducted with caregivers, rehabilitation professionals, and other stakeholders. Socio-demographic information was collected and semi-structured interviews were conducted by a research team member, recorded, transcribed and analyzed using a thematic analysis method to identify main themes related to our aim. CES University ethical review board approved this study. Results Thirty-two participants were interviewed: eight were male, 42.1 ± 11.1 years old, and 44% (n = 14) were PWDs. Three main themes were identified among all the participants: the meaning of rehabilitation, challenges to access services, and participation. Challenges to access services had three sub-themes: barriers to personal mobility, perceptions and knowledge on disability, and navigating the system. Conclusion The main focus of rehabilitation as perceived by stakeholders is still on functional rehabilitation. If healthcare personnel is better trained on disability and if those with disabilities are actively involved in the developing these programs, the focus may evolve to a comprehensive and equitable rehabilitation process that fosters full participation.